Unraveling the Excitonic Transition and Associated Dynamics in Confined Long Linear Carbon Chains with Time‐Resolved Resonance Raman Scattering. Issue 12 (28th October 2021) - Zhu, Jingyi; Bernhardt, Robin; Cui, Weili; German, Raphael; Wagner, Julian; Senkovskiy, Boris V.; Grüneis, Alexander; Pichler, Thomas; Li, Yuxuan; Li, Xueyang; Wu, Kaifeng; Liu, Rulin; et al.
Abstract: Long linear carbon chains are attracting intense interest arising from their remarkable properties, such as the tunable direct energy gap, the high mechanical hardness, and the high Raman response cross section, which would play a great role in their potential applications in future nanotechnology. Here the excitonic transitions and the associated relaxation dynamics of nanotube confined long linear carbon chains are comprehensively interrogated by using steady state and time‐resolved Raman spectroscopies. The exciton relaxation dynamics of the confined carbon chains occurs on a hundred of picoseconds timescale, in strong contrast to the host dynamics that occurs on a few picoseconds' timescale. A prominent time‐resolved Raman response is observed over a broad energy range extending from 1.2 to 2.8 eV, which includes the strong Raman resonance region around 2.2 eV. Strong coupling between the chain and the nanotube host is found from the dynamics at high excitation energies which provides clear evidence for an efficient energy transfer from the host carbon nanotube to the chain. The experimental study presents the first unique characterization of the long linear carbon chain exciton dynamics, providing indispensable knowledge for the understanding of the interactions between different carbon allotropes. Abstract : Confined long linear carbon‐chains have extremely broad optical responses and strong excited state interactions with their host carbon nanotubes.